A comparative pharmacological study of three Chinese traditional medicines found Blautia to be the key functional bacterium of Coptis chinensis Franch. and Phellodendri chinensis Cortex against colitis - Zhan, Jiaguo; Cheng, Jiale; Yang, Yanan; Xu, Xiaofan; Lu, Zhiyi; Li, Leilei; Li, Haoyu; Yang, Qiannan; Hu, Yanran; Song, Yuxin; Fan, Qingmiao; Yang, Enwei; et al. (Frontiers in Pharmacology, 2025)
BackgroundSanhuang refers to the three cold-natured and bitter-flavored traditional Chinese medicines, namely, Scutellaria baicalensis Georgi (HuangQin, HQ), Coptis chinensis Franch. (HuangLian, HL), and Phellodendri chinensis Cortex (HuangBo, HB). Although similar in drug properties, they are traditionally used to treat different dampness-heat syndromes belonging to the Upper Jiao (lung and heart diseases), the Middle Jiao (stomach and intestine diseases), and the Lower Jiao (intestine, kidney, and bladder diseases). The mechanisms behind their differential effects remain unexplored.MethodA model of large intestine dampness-heat syndrome colitis was established through the administration of exogenous hygrothermal conditions combined with lipopolysaccharide (LPS) and Escherichia coli. This model was employed to evaluate the efficacy of Phellodendri Chinensis Cortex, C. chinensis Franch., and S. baicalensis Georgi. Full-length 16S rRNA amplicon sequencing was utilized to assess changes in gut microbiota following drug interventions. Ultimately, the therapeutic effects of key microbial strains on ulcerative colitis were confirmed using a dextran sulfate sodium (DSS)-induced colitis model.ResultsThe results showed that HL and HB exhibited significant remedial effects on large intestine dampness-heat syndrome (LIDHS) colitis, but HQ did not. Gut microbial analysis revealed that HL and HB markedly shifted the overall structure of gut microbiota, while HQ showed little impact. The increase of Blautia sp. was a common sign in both HL- and HB-treated animals, but it was not observed in the HQ group. On the contrary, the abundance of a Lactobacillus-dominant co-abundance gene group (CAG) significantly declined in the HL and HB groups but was similar to the negative control in the HQ group. Additionally, our observations indicate that the enrichment of Blautia is consistent with the difference in drug efficacy. In vivo experiments also demonstrated the anti-colitis efficacy of Blautia producta.ConclusionThis study identifies Blautia as the key bacterium against ulcerative colitis through the establishment of a novel model and a drug comparison.